UPAYA PENGENALAN BUDAYA LOKAL MELALUI PEMBELAJARAN BERBASIS KEARIFAN LOKAL PADA ANAK USIA DINI - Intan Yudha Prastika; Adis Adela Putri; Tari Patunnisa; Fauzi Kurniawan; Jubaidah Hasibuan (STKIP Subang, 2026)
This study addresses the limited effectiveness of local culture introduction in early childhood education, where cultural learning is often delivered superficially without integrating local wisdom values. The objective of this research is to describe the implementation of local wisdom-based learning in introducing local culture to early childhood, identify the forms of learning activities used, and examine teachers’ efforts in enhancing children's cultural understanding. This study employs a qualitative approach with a descriptive method. Data were collected through observation of classroom activities, interviews with teachers, and documentation of learning processes in early childhood education settings. The results indicate that local wisdom-based learning can be effectively implemented through various activities such as introducing traditional clothing, traditional games, local songs, storytelling, and the use of culturally relevant learning media. Teachers play a crucial role in designing contextual and engaging learning experiences that align with children's developmental characteristics. Such approaches enable children to understand and appreciate their local culture more meaningfully. Therefore, integrating local wisdom into early childhood learning is an effective strategy to foster cultural awareness, strengthen identity, and cultivate a sense of pride and love for local heritage from an early age.